Norwegian Public Library Language Cafés Facilitate Discourse Between Immigrants and Norwegian-Born Citizens - Krueger, Stephanie (Evidence Based Library and Information Practice, 2018)
A Review of: Johnston, J., & Audunson, R. (2017). Supporting immigrants’ political integration through discussion and debate in public libraries. Journal of Librarianship and Information Science, 29 May, 1-15. https://dx.doi.org/10.1177/0961000617709056 Abstract Objective – To investigate if conversation-based language cafés in Norway provide a platform for improving communication between immigrants and Norwegian-born citizens, potentially setting the stage for better participation by immigrants in civic dialogues. Design – Multi-site case study. Setting – Public libraries in Oslo, Moss, and Horten, Norway. Subjects – Language café participants (immigrants and Norwegian-born volunteers). Methods – Participant observation and questionnaires for immigrants (Norwegian, English, Somali, and Arabic language versions) and volunteers (Norwegian language only) who took part in café activities. Main Results – 64 immigrants (21 in Oslo, 30 in Moss, 13 in Horten) and 31 volunteers (7 in Oslo, 14 in Moss, 10 in Horton) completed questionnaires. Language cafés at all three sites led to informal, respectful discursive interaction between participants. Though each café had a unique set of participants and conversational topics, all cafés enabled immigrants to improve their Norwegian language skills while providing all participants with a place to meet new people, exchange information, and discuss political issues. Conclusion – Having attended the cafés and improved their knowledge of Norwegian language and culture, immigrants at all three sites were potentially better equipped for future participation in the Norwegian public sphere.